Performance Evaluation of Routing for Wireless Sensor Network - N, Saranya; K, Manimekalai (International Journal of Computer Sciences and Engineering, 2020)
Wireless Sensor Network (WSN) is consisting of independent and distributed sensors to monitor physical or environmental conditions, such as temperature, sound, pressure, etc. Routing protocols represent an essential aspect of the performance of mobile wireless networks. This paper presents a comparative analysis between several routing algorithms and their impact on the performance of WSN. In this paper, we used NS-2 to simulate and implemented routing protocols like Destination-Sequenced Distance-Vector Routing (DSDV) protocol, Ad hoc On-Demand Distance Vector (AODV) protocol, Optimized Link State Routing Protocol (OLSR) protocol and Dynamic Source Routing (DSR) protocol for many numbers of nodes. We compared network parameters, analyzed and evaluated the performance with comparing the end to- end delay, packet delivery fraction (PDF), throughput and packet loss rate. As the number of nodes increases and the network expands, the performance of the AODV protocol obtains better results than the other protocols.